- Thread starter
- Admin
- #1

- Jan 26, 2012

- 4,093

--------------------

Remember to read the POTW submission guidelines to find out how to submit your answers!

- Thread starter Jameson
- Start date

- Status
- Not open for further replies.

- Thread starter
- Admin
- #1

- Jan 26, 2012

- 4,093

--------------------

Remember to read the POTW submission guidelines to find out how to submit your answers!

- Thread starter
- Admin
- #2

- Jan 26, 2012

- 4,093

1) Reckoner

Solution (from Reckoner):

\[\begin{eqnarray}m = \frac{m_0}{\sqrt{1 - v^2/c^2}} & \Rightarrow & \sqrt{1 - \frac{v^2}{c^2}} = \frac{m_0}m\\&\Rightarrow& 1-\frac{v^2}{c^2} = \frac{m_0^2}{m^2}\\&\Rightarrow& v^2 = c^2\left(1 - \frac{m_0^2}{m^2}\right)\\&\Rightarrow& v = c\sqrt{1 - \frac{m_0^2}{m^2}}\\&\Rightarrow& f^{-1}(m) = c\sqrt{1 - \frac{m_0^2}{m^2}}\end{eqnarray}\]

We may verify that \(f\) and \(f^{-1}\) are inverses by observing that

\[\left(f\circ f^{-1}\right)(m) = \frac{m_0}{\sqrt{1 - \left(c\sqrt{1 - m_0^2/m^2}\right)^2/c^2}} = m\]

and

\[\left(f^{-1}\circ f\right)(v) = c\sqrt{1 - \frac{m_0^2}{\left(m_0/\sqrt{1 - v^2/c^2}\right)^2}} = v.\]

- Status
- Not open for further replies.